The impacts of adult death on child growth and nutrition evidence from five southern African countries - Brunelli, Chiara; Kenefick, Eric; Yamauchi, Futoshi (International Food Policy Research Institute, 2008)
The AIDS epidemic has caused a drastic increase in adult mortality. This study examines the impacts of adult deaths on child nutrition—specifically the impact on child food intake and growth with reference to their weights. Anthropometry data from five southern African countries are analyzed for this purpose, and we adopt new methods to investigate the impacts of (recent) adult deaths on short-run changes in child weight. If households face credit constraints, and their risk mitigating strategies do not ensure perfect smoothing of consumption, the death of adult members (who are likely income earners) can decrease consumption and therefore dietary intakes. Weight is a good measure of the nutritional status of children, and, because children are highly vulnerable members of the household, of the household’s welfare.